Multi-scale analysis of the progressive failure behaviour of 2.5D woven SiC/SiC composites under compression - Chenyu Yang; Chao You; Weilong Wu; Qiyu Wu; Xiguang Gao; Fang Wang; Yingdong Song (Journal of Materials Research and Technology)
The compressive behaviour of 2.5D woven SiC/SiC composites is investigated in this paper. Compressive tests of 2.5D woven SiC/SiC composites were firstly conducted to obtain the compressive strength and the constitutive relationship. The evolution of surface strain distributions implying the trends of damage accumulation were obtained using digital image correlation (DIC) during the test. Subsequently, the microscale and mesoscale failure modes of the specimens were comprehensively characterised using X-ray computed tomography (X-CT) and scanning electron microscopy (SEM). To simulate the damage evolution process of specimens, a multi-scale finite element model representing the meso-scale structure of 2.5D SiC/SiC composites was developed, in which the proposed progressive damage method emphasising on matrix damage was adopted. This model was demonstrated to be capable of accurately predicting the compressive stress-strain curve and damage evolution of 2.5D SiC/SiC composites, showing good consistency with experimental characterisations.